Protestant anthropology: between secularity and postsecularity - Tetiana Gavryliuk (Українське Pелігієзнавство, 2015)
Protestant anthropology: between secularity and postsecularity. In this article the analysis of main problems of the Protestant anthropology late XX – early XXІ centuries. It is shown that the theological discourse on the merits of the man and his life unfolded within the paradigm of secular and post-secular.